Influencia de la Carga de Trabajo en el Ausentismo del Personal Médico de Salud Mental en Mexicali, Baja California - Roberto López López; Gendi del Rosario Leyva Castro; Cesar David Elizalde González (Ibero Ciencias - Revista Científica y Académica - ISSN 3072-7197, 2026)
This study investigates the relationship between workload and absenteeism among medical staff at a mental health institution. The main objective is to determine the influence of workload and how it affects the prevalence of absenteeism among medical personnel. A quantitative correlational study was conducted using a sample of 96 employees from the medical department. Surveys were administered to collect data on how workload contributed to stress and other symptoms that led these individuals to be absent from work. The findings suggest that workload directly affects employees physically and mentally, consequently causing them to miss work and increasing the workload for those who do attend. In conclusion, it is recommended that psychological therapy spaces be created where employees can release and manage stress during their workdays in order to prevent these incidents from happening. In addition, further research is recommended to explore other types of effects experienced by employees that may contribute for this incident to happen.